2018
DOI: 10.1007/s00374-018-1279-4
|View full text |Cite
|
Sign up to set email alerts
|

Dung application increases CH4 production potential and alters the composition and abundance of methanogen community in restored peatland soils from Europe

Abstract: who kindly helped in carrying and spreading dung to experimental sites and in sampling in Finland, Wilfried Bock for guidance and Steffen Kaufmane for s ampling the sites in Germany. Furthermore, we thank Risto Linnainmaa for dung for the field experiment, Tero Tuomivirta for discussions regarding qPCR and Sirpa Tiikkainen for guidance in cloning and sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Methanogenesis is an anaerobic decomposition process that forms the terminal step, and is implemented by members of the phylum Euryarchaeota [14,19]. Recently, several studies have concluded that the mcrA gene is an effective phylogenetic marker for exploring methanogens in peatland soil, lake sediment, and natural or constructed wetland [14,[20][21][22]. In wetlands, there are two primary groups of methanogens: acetoclastic methanogens and hydrogenotrophic methanogens [23].…”
mentioning
confidence: 99%
“…Methanogenesis is an anaerobic decomposition process that forms the terminal step, and is implemented by members of the phylum Euryarchaeota [14,19]. Recently, several studies have concluded that the mcrA gene is an effective phylogenetic marker for exploring methanogens in peatland soil, lake sediment, and natural or constructed wetland [14,[20][21][22]. In wetlands, there are two primary groups of methanogens: acetoclastic methanogens and hydrogenotrophic methanogens [23].…”
mentioning
confidence: 99%